O direito à consulta prévia no caso Belo Monte: percepção do outro, para além do reconhecimento jurídico e do individualismo - Schütz, Gleirice Machado (Universidade do Vale do Rio dos Sinos, 2020)
This paper discusses the indigenous right of free and informed prior consultation, about the construction of the Belo Monte Hydroelectric Plant. The main focus of the research was to verify in which level this right to prior consultation, formally fixed in many normative documents, was effective, which are the possible fundamentals of this (in)effectiveness and what are the alternatives to the problem. Once this research is characterized by the study of an empirical object, but legally, historically, anthropologically and philosophically questioned, the methodology consisted, mainly, of bibliographic and documental research, from a transdisciplinary perspective, using a dialectical approach and also case studies. In this sense, it was found that the formation of Brazilian society, configured by individualism forged in Western modernity, the context in which human rights have emerged, created a strong resistance to the effectiveness of the rights of traditional societies. In the case of the right to prior consultation about Belo Monte enterprise, considering the collected data and information in the field of facticity, as well as the production and application of law, it is concluded that there is no effectiveness, in contemporary, once this right is used as a mere instrument of acknowledgement, because the indigenous do not participate effectively in the decisions, even if these ones affect them directly. Therefore, as an alternative to the promotion and delivery of such right, this paper proposes a paradigm shift toward interculturalism and to otherness as key vectors for production and implementation of the right of the traditional societies, including the indigenous people.
Keywords: Consulta; Prévia; Indígenas; Modernidade; Individualismo; Interculturalismo; Alteridade; Belo Monte; Consultation; Preview; Indigenous; Modernity; Individualism; Interculturalism; Otherness; ACCNPQ::Ciências Sociais Aplicadas::Direito